2017
DOI: 10.1038/s41528-017-0005-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive flexible broadband photodetectors achieving pA scale dark current

Abstract: Organolead halide perovskite is a newly emerging low-cost, solution-processable material with a broadband absorption from the ultraviolet (UV) to visible (Vis) region, which has attracted a great deal of interest in high-performance optoelectronic devices. However, some practicable applications need a cover of UV-Vis-NIR region for photoelectric conversion, a task that remains a significant challenge for further extending the absorption toward the near-infrared radiation (NIR) region. Here, to the best of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 44 publications
1
27
1
Order By: Relevance
“…The responsivity and detectivity of self‐powered photodetectors obtained in the present study were compared with reported perovskite‐based sandwiched‐type devices, as shown in Figure . [ 8,19,42,45–52 ] The responsivity and detectivity reported in the present study are superior compared with prior relevant studies. The superior performance obtained from self‐powered photodetectors via CVD deposited perovskite films might be attributed to the high intrinsic quality of the perovskite films (high quality compact films and with no pinholes).…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The responsivity and detectivity of self‐powered photodetectors obtained in the present study were compared with reported perovskite‐based sandwiched‐type devices, as shown in Figure . [ 8,19,42,45–52 ] The responsivity and detectivity reported in the present study are superior compared with prior relevant studies. The superior performance obtained from self‐powered photodetectors via CVD deposited perovskite films might be attributed to the high intrinsic quality of the perovskite films (high quality compact films and with no pinholes).…”
Section: Resultscontrasting
confidence: 62%
“…In particular, with exposure to red (632 nm) illumination, devices made with pure and bromine‐doped MAPbI 3 films showed the highest photoresponse when compared with illumination in the blue (465 nm) and green (528 nm) regions ( Figure a and Figure S8a, Supporting Information) similar to the trend reported in the literature. [ 41,42 ] As expected, the MAPbI 3‐ x Br x devices showed a large photocurrent (mA) at all of the wavelengths compared with the pure‐iodide devices, which could be attributed to the longer PL‐carrier lifetime and superior charge‐transport properties of the MAPbI 3‐ x Br x films (Figure 4a and Figure S9, Supporting Information). Based on the photocurrent measurements, the performance metrics such as responsivity ( R ), specific detectivity ( D *), and external quantum efficiency (EQE) were calculated in order to evaluate the photodetector performance quantitatively (Figure 4b,c and Figure S8b, Supporting Information).…”
Section: Resultssupporting
confidence: 56%
“…Recent efforts seek to integrate perovskite photodetectors on low‐temperature flexible substrates such as polyethylene terephthalate and polyimide . Previous reports in this direction include a self‐powered device using a CH 3 NH 3 PbI 3 and Spiro‐OMeTAD composite film atop carbon cloth, a broadband device using a PbPc/MAPbI 3− x Cl x thin film, intertwined fibrous perovskite–carbon fiber devices, and a CH 3 NH 3 PbI 3 thin film device deposited by vapor solvent method . Although the device performances improved, the growth of the thin active layer on the flexible substrate generates significant challenges including poor thin film coverage and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Later, lead phthalocyanine (PbPc), a kind of organic dyes with high NIR light absorption ability were utilized to extend optical response range of the perovskite PDs. Luo et al developed a flexible broadband photodetector using PbPc/MAPbI 3‐x Cl x complex films, which manifested excellent photo‐sensitivities in the ultraviolet to near infrared region with pA scale dark current . The perovskite film reported here have a porous structure, which can promote light absorption by a larger surface‐to‐volume ratio and hamper carriers transfer in darkness by more grain boundary.…”
Section: Flexible Photodetectors Based On Metal Halide Perovskitesmentioning
confidence: 98%
“…In addition to organic semiconductor materials, other organic materials such as Rhodamine, phthalocyanine dyes, porphyrin, chlorophyll etc. also have been applied in PDs . For example, Xie et al designed a planar flexible photodetector with a bulk‐heterojunction architecture by spinning MAPbI 3 and Rhodamine B (RhB) precursor solutions on plastic substrate with interdigitated Au electrodes .…”
Section: Flexible Photodetectors Based On Metal Halide Perovskitesmentioning
confidence: 99%